Grammatical gender assignment in French: dispelling the native speaker myth. Issue 1 (20th July 2017) - AYOUN, DALILA
ABSTRACT: This study highlights the complexity of French grammatical gender as a lexical property at the interface of morpho-phonology and the lexicon. French native speakers (n = 168) completed a gender assignment task with written stimuli illustrating common versus uncommon nouns, vowel-initial versus consonant-initial nouns, compounds and grammatical homonyms; they also indicated the strategies they used to assign a gender to stimuli. The findings showed strong lexical and gender effects suggesting that grammatical gender must be acquired for individual lexical items as morpho-phonological cues alone are unreliable and vary greatly.